Entre los programas de transferencias condicionadas de ingresos y las asignaciones familiares: disputas por los sentidos alrededor de la Asignación Universal por Hijo para Protección Social en Argentina - De Sena, Angélica; Cena, Rebeca; Dettano, Andrea (Revista del CLAD Reforma y Democracia, 2018)
AbstractThis article aims to conduct a conceptual study around a particular type of social policy such as the Universal Child Allowance for Social Protection (AUH), implemented in Argentina in 2009. This is a social intervention of the State through a cash transfer to households in poverty conditions with children under 18 years. The AUH creation occurred through a Necessary and Urgent Decree (1602/09) and was conceptualized as an extension of the Family Allowances Regime. There was a broad debate focused on establishing whether the AUH could be think a Conditional Cash Transfer Program -due to the profile adopted by the program- or as a type of the Family Allowance System. This document will try to consider this. For this purpose, the paper: a) analyses the AUH in relation to the central components of the Conditional Cash Transfers; b) exposes the AUH history in relation to the Family Allowances System; c) considers the recipient families’ definition of the situation; and d) introduces some final reflections as a starting point of debate for future approaches that take into account the different discussions and meanings of the State’s interventions proposed here.